IDENTIFIKASI FAKTOR USER EXPERIENCE DARI KONSEP DESIGN FOR HAPPINESS - Devanny Gumulya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
This paper aims to identify User Experience (UX) factors from the Design for Happiness (DfH) concept. UX is an important aspect in product design that aims to enhance user happiness and well-being. The study involves a literature review of the understanding of the design for happiness concept and existing UX factors. The identified UX factors are then connected to the components of design for happiness, and these faktors are formulated and applied in the form of an application prototype. Subsequently, an evaluation is conducted to provide valid and specific descriptions of UX factors from the design for happiness concept. The research findings identify four UX factors of design for happiness: intuitiveness, progress monitoring, personalization, and option variation. These factors serve to create user experiences that meet psychological and emotional needs, provide ease in achieving goals, allow for personalization based on individual preferences, and offer adequate choices to users. The findings of this research are expected to provide valuable insights for product designers in considering UX factors from the Design for Happiness (DfH) concept during the design process, with the goal of creating more satisfying experiences for users when interacting with digital products and positively impacting user happiness.